The Third Initial-Boundary Value Problem for a Class of Parabolic Monge-Ampère Equations (Communications in Mathematical Research, 2021)
For the more general parabolic Monge-Ampère equations defined by theoperator $F(D^2u + σ(x))$, the existence and uniqueness of the admissible solution tothe third initial-boundary value problem for the equation are established. A newstructure condition which is used to get a priori estimate is established.